AN ERROR ANALYSIS OF USING PAST TENSE IN WRITING NARRATIVE TEXT AT THE ELEVENTH GRADE STUDENTS AT SMA NEGERI 5 BINJAI AND SMA NEGERI 7 BINJAI - Ricka Setiawati; Anni Holila Pulungan (Universitas Negeri Medan, 2015)
This research deals with an error analysis. The objective of the study are (1) to identify and classify the kinds of past tense error find in narrative writing by the eleventh grade students at SMA Negeri 5 Binjai and At SMA Negeri 7 Binjai, (2) to find out the causes of past tense error in narrative writing by the eleventh grade students at SMA Negeri 5 Binjai and at SMA Negeri 7 Binjai. The research design that was used in this study descriptive research. The sources of data were taken from the eleventh grade students of SMA Negeri 5 Binjai which consists of 40 students who were chosen by taking the X-1 class as the sample. And in SMA Negeri 7 Binjai which consists of 40 students who were chosen by taking the X-3 class as the sample. In this research, the writing text was used as collecting data. The result of the analysis shows that: (1) the errors of past tense in narrative writing made by the eleventh grade students of SMA Negeri 5 Binjai were 141 occurrences of all errors. And in SMA Negeri 7 Binjai were 166 occurrences of all errors. Keywords : Error Analysis, Past Tense